Respostas

2013-12-03T11:20:25-02:00
Use Bhaskara -> (delta) = b^2 -4. a.c
X= -b +ou - raiz quadrada de (delta) : 2.a
Na equação Ax^2 +/- Bx +/- c
2013-12-03T11:43:53-02:00
Bem, vejamos...
Por exemplo:
x² - 13x + 36 = 0
a = 1, b = -13, c = 36
Δ = b²-4ac
Δ = (-13)² - 4.1.36
Δ = 169 - 144
Δ = 25
x = (-b+/-\/Δ)/2a
x = [-(-13)+/-\/25]/2.1
x = (13+/-5)/2
x' = (13+5)/2 --> x' = 18/2 --> x' = 9
x" = (13-5)/2 --> x" = 8/2 --> x" = 4
Solução: {4;9}
Este é o modo como resolvemos uma equação do segundo grau (um dos modos).